PEMBERIAN ASI EKSKLUSIF DAN STATUS GIZI SERTA HUBUNGANYA TERHADAP KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS JUNTINYUAT - Ade Rahmawati (Universitas Wiralodra, 2019)
Diarrhea is an increase in the number of bowel movements (3 times or more) accompanied by changes in the consistency of stool (becoming more watery or runny) within 24 hours.Diarrhea is still a global problem and many are infected in developing countries with poor environmental sanitation conditions, insufficient water supply, poverty, and low education.The incidence of diarrhea varies in each region in each region, season, and endemic periods.The purpose of this study was to determine the relationship between exclusive breastfeeding and nutritional status with the incidence of diarrhea in infants in the work area of ​​Juntinyuat Health Center. This type of research was observational analytic using a cross sectional study design. The population in this study was all toddlers aged 12-59 months who were in the working area of ​​the Juntinyuat Health Center as many as 270 toddlers who had cards to health. The sample in this study was toddlers aged 12-59 months who were selected as samples in the working area of ​​Juntinyuat Health Center as many as 69 children. How to take samples with Simple Random Sampling. Based on the results of statistical tests obtained the value of bivariate analysis, namely exclusive breastfeeding (p value = 0.001) and nutritional status (p value = 0.002) related to the incidence of diarrhea in infants in the work area of ​​Juntinyuat Health Center.It is expected that mothers who have toddlers should always give exclusively and maintain the nutritional status of children to prevent the occurrence of diarrheal diseases.